Ocular disorders in multiple myeloma patients: cross-sectional study of prevalence and association with treatment. Issue 2 (28th January 2019) - Pennisi, Martina; Berchicci, Luigi; Miserocchi, Elisabetta; Mussetti, Alberto; Cacioppo, Viviana; David, Alessandro; Scialdone, Antonio; Lorusso, Ilaria; Modorati, Giulio; Corradini, Paolo; Montefusco, Vittorio
Abstract: Multiple myeloma (MM) therapy is evolving, and several new drugs are now available, extending patients' life and exposure to different compounds and toxicities. We conducted a cross-sectional observational study enrolling 93 consecutive patients on active treatment for MM, aiming to assess their ocular complications. All the patients underwent a comprehensive ophthalmic evaluation. In our cohort, prevalence of low visual acuity was in line with similar age healthy population reported in registry studies. Interestingly, we recorded a higher prevalence of lens opacities (46%) and dry eye syndrome (53%). Nevertheless, we did not find any significant association between ocular disorders and anti-myeloma treatments, even steroid therapy. This observation suggests that other factors besides treatments, such as M-protein deposition in eye structures, may have a role in developing ocular toxicities. Since MM patients are elderly patients at higher risk of age-related eye disorders, we recommend periodic ophthalmic assessment in daily practice.